Mortality from gastroschisis in the state of Rio de Janeiro: a 10-year series - Camilla Ferreira Catarino Barreiros; Maria Auxiliadora de Souza Mendes Gomes; Saint Clair dos Santos Gomes Júnior (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To analyze mortality and associated factors in a series of gastroschisis at birth in the state of Rio de Janeiro in a 10-year period (2005 to 2014). METHOD A retrospective cohort study, which related the databases of the Live Births Information System and the Mortality Information System by probabilistic linkage. Final database was constructed in two stages: preparation of the two initial databases and establishment of relationships between them. RESULTS Preterm newborns and those with low birthweight had higher risk of death, with statistical significance (p = 0.03 and p = 0.006, respectively). Regarding place of birth, although death frequency was higher in maternity units than in general hospitals (p = 0.04; OR = 0.5; 95%CI 0.3-1.0), it was observed that a unit characterized as a general hospital had a high birth frequency (61.2%). Furthermore, the comparative analysis of the risk of death between this unit and others showed a 7.5 higher risk of death in general hospitals and 3.2 higher in maternity units, with statistical significance (p < 0.001). Moreover, births in level II intensive care units had 3.9 times more risk of death compared with level III (p < 0.001). CONCLUSION This study foments the discussion of two possible strategies in the treatment of gastroschisis in newborns. First, the centralization of care in tertiary units, enabling malformation care to be analyzed in a more detailed and standardized manner. Second, and perhaps more feasible, the elaboration of clinical guidelines to standardize immediate care for gastroschisis in babies born outside tertiary centers, as well as the standardization of their transportation until arrival at the tertiary center.